2002
DOI: 10.1128/jb.184.4.1046-1056.2002
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory RNA as Mediator in GacA/RsmA-Dependent Global Control of Exoproduct Formation inPseudomonas fluorescensCHA0

Abstract: In Pseudomonas fluorescens CHA0, an antagonist of root-pathogenic fungi, the GacS/GacA two-component system tightly controls the expression of antifungal secondary metabolites and exoenzymes at a posttranscriptional level, involving the RNA-binding protein and global regulator of secondary metabolism RsmA. This protein was purified from P. fluorescens, and RNA bound to it was converted to cDNA, which served as a probe to isolate the corresponding chromosomal locus, rsmZ. This gene encoded a regulatory RNA of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
347
1
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 323 publications
(367 citation statements)
references
References 65 publications
16
347
1
3
Order By: Relevance
“…The results of the Northern blot analysis indicated that L. pneumophila expresses an ϳ500-base monocistronic letE RNA in the E phase; in the PE phase, LetA/LetS and RpoS regulate its decay. Its scarcity in the PE phase is inconsistent with the idea that letE encodes a regulatory RNA that sequesters CsrA to relieve repression of the transmission phenotype (20).…”
Section: Resultscontrasting
confidence: 38%
See 3 more Smart Citations
“…The results of the Northern blot analysis indicated that L. pneumophila expresses an ϳ500-base monocistronic letE RNA in the E phase; in the PE phase, LetA/LetS and RpoS regulate its decay. Its scarcity in the PE phase is inconsistent with the idea that letE encodes a regulatory RNA that sequesters CsrA to relieve repression of the transmission phenotype (20).…”
Section: Resultscontrasting
confidence: 38%
“…Members of this family of two-component regulators induce the expression of the csrB regulatory RNA, which sequesters the CsrA repressor, permitting the translation of target mRNAs (20). However, unlike csrB, L. pneumophila LetE appears to function as a protein, not an RNA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The best known TCST among Pseudomonas species is GacS/GacA, known as a master regulator of secondary metabolism. GacS/GacA is essential for phenazine production in P. chlororaphis (Chancey et al, 1999(Chancey et al, , 2002 and other pseudomonads (Heeb et al, 2002). Upon activation by as-yet undetermined signals, the membrane-bound HK sensor GacS activates the GacA RR by phosphorylation.…”
Section: Introductionmentioning
confidence: 99%